1996
DOI: 10.4218/etrij.96.0196.0037
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Conformation and Application of Stereoregular PMMA Langmuir-Blodgett Films

Abstract: Molecular conformations of stereoregular poly(methyl methacrylate) (PMMA) monolayers have been investigated by scanning probe microscopes. Isotactic and syndiotactic PMMAs were found to have right and left hand helical structures, respectively. On the contrary atactic PMMA showed rather random arrangement of the chains. It has been demonstrated that the PMMA Langmuir‐Blodgett(LB) films can be utilized to form nanoscale patterns down to 50 nm and to form a geodesic lens. It has also been manifested that the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In polar polymers, the situation can be much more complicated and the apparent surface potential of polymer molecules has to be discussed in connection with macroscopic Kelvin probe studies of thin PMMA films. These studies revealed that surface potential of PMMA films depends on the stereoregularity and molecular conformations of this polymer [ 21 ]. Therefore, PMMA domains and blocks in multi-component polymer materials might exhibit a specific surface potential that can be examined with KFM.…”
Section: Resultsmentioning
confidence: 99%
“…In polar polymers, the situation can be much more complicated and the apparent surface potential of polymer molecules has to be discussed in connection with macroscopic Kelvin probe studies of thin PMMA films. These studies revealed that surface potential of PMMA films depends on the stereoregularity and molecular conformations of this polymer [ 21 ]. Therefore, PMMA domains and blocks in multi-component polymer materials might exhibit a specific surface potential that can be examined with KFM.…”
Section: Resultsmentioning
confidence: 99%
“…In expansion of the range of polymer materials that can be examined with KFM, we consider acrylic polymers. Macroscopic Kelvin probe studies of thin PMMA films revealed that their surface potential depends on stereoregularity and molecular conformations of this polymer (Kim et al, 1996). Therefore, surface PMMA domains and blocks in multicomponent polymer materials might exhibit a specific surface potential.…”
Section: Resultsmentioning
confidence: 99%
“…It means that interaction between azobenzene molecules occur. At the same time, some interaction between azobenzene derivative and s-PMMA polymer (the dipole moment is of 0.17 D [9]) takes place too. As the example, in Fig.…”
Section: Estimation Of the Photoisomerization Kineticsmentioning
confidence: 99%